Gewerkschaften - Revitalisierung oder Niedergang? Eine beispielhafte Analyse anhand des Phänomens Cloudworking - Schwartz, Marcel (Young Academics: Soziologie, 2023)
The situation of the DGB trade unions has been interpreted disparately since the end of the 2000s. For one side, they are experiencing a comeback. For the other, the decline that has been attested since the beginning of the 21st century is continuing. In order to resolve this contradictory interpretation, the Strategic Unity working group proposes a change of perspective: Scholarly work should primarily analyse which options for action and resources trade unions have and use to solve their crisis. Marcel Schwartz takes up this suggestion in his qualitative study and analyses revitalisation processes of IG-Metall and ver.di on the basis of the phenomenon of cloudworking. He then places his findings in the debate outlined above.